Computational Model of Boride Diffusion Layer on the Low Carbon Steel - Sutrisno, Sutrisno (Al-Fiziya: Journal of Materials Science, Geophysics, Instrumentation and Theoretical Physics, 2023)
In this paper, a computation model was used  to analysis  the growth kinetic of two boride layers FeB and Fe2B on the surface of low carbon steel. St41 one of the low carbon steel was used as the basic sample and given the treatment by adding the powder pack boriding in the temperature of 700, 800, and 9000C for the 8 hours of treatment time. To perform the morphology and dimension of the boride layers used the optical microscope. The computation model based on the diffusion equation from the Fick’s Law and solved under the certain assumptions with the parabolic growth of iron boride. For this study, a numerical method was created to determine the iron borides layer thickness as a function of process parameters (temperature and time).By using the parabolic growth constant  it can be determined the diffusion coefficient for the phase of FeB, Fe2B, and diffusion zone. Based on the diffusion coefficient it can be predicted the depth and thickness of borided layer on the surface of St41 low carbon steel